Association Between Pre-Pregnancy Body Mass Index and Maternal and Neonatal Outcomes of Singleton Pregnancies After Assisted Reproductive Technology - Sun, Hanxiang; Liu, Yang; Huang, Shijia; Liu, Xiaosong; Li, Guohua; Du, Qiaoling (Frontiers in Endocrinology, 2022)
Objective To study the association between pre-pregnancy body mass index (BMI) and adverse maternal and neonatal outcomes of singleton pregnancies after assisted reproductive technology (ART). Methods This hospital-based retrospective cohort study of women with live singleton births through ART in China from January 2015 to August 2020 included 3043 Chinese women. According to the latest BMI classification standard of Asian women, the women included in this study were classified as underweight (BMI <18.5 kg/m2), normal (BMI 18.5 to <23 kg/m2), overweight (BMI 23 to <27.5 kg/m2), and obese (BMI ≥27.5 kg/m2). We compared the risk of adverse outcomes of different pre-pregnancy BMI values of women with singleton pregnancies conceived through ART.We used Logistic regression analysis to estimate the associations between pre-pregnancy BMI and adverse perinatal and neonatal outcomes. Results Our findings showed that women who were overweight or obese before pregnancy through ART are more likely to have a cesarean section, gestational diabetes mellitus, gestational hypertension, and preeclampsia, regardless of whether confounding factors are adjusted. Moreover, pre-pregnancy obesity was more associated with a higher risk of these adverse outcomes than pre-pregnancy overweight. In addition, neonates from women who had obesity before pregnancy through ART were more likely to have macrosomia; adjusted odds ratios and 95% confidence intervals were 3.004 (1.693-5.330). Conclusions Our research showed that women who had pre-pregnancy overweight or obesity with singleton pregnancies through ART were more likely to have a cesarean section, gestational diabetes mellitus, gestational hypertension, and preeclampsia. Moreover, neonates from women who had obesity before pregnancy were more likely to have macrosomia.